Persona Rights for User-Generated Content: A Normative Framework for Privacy and Intellectual Property Regulation - Tamara Shepherd (tripleC: Communication, Capitalism & Critique)
This article introduces the term “persona rights” as a normative conceptual framework for analyzing the language of regulatory debates around privacy and intellectual property online, mainly from a Canadian perspective. In using the concept of persona rights to interrogate and critique the current limitations of regulatory discourses in protecting user rights online, the legal implications of persona rights law are translated into more conceptual terms. As a normative framework, persona rights is shown to be useful in addressing the gaps in regulatory understandings of privacy and intellectual property – particularly in spaces for user-generated content (UGC) – and in suggesting how policy might be written to account for user rights to the integrity of identity in commercial UGC platforms.